Long-Term Impact of a Cell Phone–Enhanced Parenting Intervention. (November 2017) - Lefever, Jennifer E. Burke; Bigelow, Kathryn M.; Carta, Judith J.; Borkowski, John G.; Grandfield, Elizabeth; McCune, Luke; Irvin, Dwight W.; Warren, Steven F.
Home visiting programs support positive parenting in populations at-risk of child maltreatment, but their impact is often limited by poor retention and engagement. The current study assessed whether a cellular phone–supported version (PCI-C) of the Parent-Child Interactions (PCI) intervention improved long-term parenting practices, maternal depression, and children's aggression. Low-income mothers ( n = 371) of preschool-aged children were assigned to one of the three groups: PCI-C, PCI, and a wait-list control (WLC) group. Parenting improved in both intervention groups between baseline and 12-month follow-up compared to the WLC. Children in the PCI-C group were rated to be more cooperative and less aggressive than children in the WLC. The results offer evidence of the long-term effectiveness of PCI and the additional benefits of cellular phone supports for promoting intervention retention and improving children's behavior.